Beauty ideals and Advertising values: A content analysis of 1950s and 1969s Number Seven printed advertisements. - Luo, shiyu (2016)
This dissertation studies the advertising values and beauty ideals using the sample of 93 printed advertisement of Number Seven from 1950s to 1960s. The research reviews the opinions provided by various scholars involving the development of beauty ideals and advertising values.Also,it introduces the history of Number Seven from the very beginning to the contemporary days and explains the reason why this research concentrates on the 1950s and 1960s.Based on these literature, this dissertation conducts content analysis to code the dominant and subsidiary advertising values and beauty ideals which manifest in the printed advertisements.From the coding result, there are two points could be concluded.Firstly,it is quite important to consider whether the advertising values and beauty ideals that the advertisements show are consistent with the social backgrounds,brand strategy,and brand aims. Secondly,it deserves attention that the prevalence of classic beauty ideal could shape the similar beauty ideal worldwide.